Unsteady MHD plane couette-poiseuille flow of fourth-grade fluid with thermal radiation, chemical reaction and suction effects - Joseph, Kpop Moses; Ayankop-Andi, Emem; Mohammed, Sani U. (Zielona Góra: Uniwersytet Zielonogórski)
This study investigates the unsteady MHD flow of a fourth-grade fluid in a horizontal parallel plates channel. The upper plate is oscillating and moving while the bottom plate is stationary. Solutions for momentum, energy and concentration equations are obtained by the He-Laplace scheme.
Keywords: thermal radiation; MHD; chemical reaction; fourth-grade fluid; suction; He-Laplace